Student Learning Outcomes: Innovative Learning with an Experimentation Blended Learning Model - Anggraini Pratiwi; Nurul Azizah; Baharudin Baharudin; M. Indra Saputra; Muhammad Mustofa (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2025)
This study aims to evaluate the effectiveness of using a blended learning model in improving students' learning outcomes in Islamic Education at SMA Negeri 1 Katibung. The research followed a quantitative approach with an experimental design and a post-test only control group method. The sample included two classes: a control group using traditional teaching methods and an experimental group applying the blended learning model. A multiple-choice test, which was validated for reliability and validity, was used to assess students' learning outcomes after the treatment. The data collected was analyzed using a t-test to compare the learning outcomes between the groups. Normality tests for both groups showed that the data followed a normal distribution, with a significance value of 0.060 (greater than 0.05). Homogeneity tests confirmed the data was homogeneous, with a significance value of 0.212 (greater than 0.05). The t-test results, including Levene’s Test for Equality of Variances, indicated a significance value of 0.113 (greater than 0.05). Based on these results, it was concluded that the Quizizz-based blended learning model did not have a significant impact on students’ learning outcomes, suggesting that the model was not effective.